Polypyrimidine-tract-binding protein: a multifunctional RNA-binding protein. (22nd July 2008) - Sawicka, Kirsty; Bushell, Martin; Spriggs, Keith A.; Willis, Anne E.
Abstract : PTB (polypyrimidine-tract-binding protein) is a ubiquitous RNA-binding protein. It was originally identified as a protein with a role in splicing but it is now known to function in a large number of diverse cellular processes including polyadenylation, mRNA stability and translation initiation. Specificity of PTB function is achieved by a combination of changes in the cellular localization of this protein (its ability to shuttle from the nucleus to the cytoplasm is tightly controlled) and its interaction with additional proteins. These differences in location and trans -acting factor requirements account for the fact that PTB acts both as a suppressor of splicing and an activator of translation. In the latter case, the role of PTB in translation has been studied extensively and it appears that this protein is required for an alternative form of translation initiation that is mediated by a large RNA structural element termed an IRES (internal ribosome entry site) that allows the synthesis of picornaviral proteins and cellular proteins that function to control cell growth and cell death. In the present review, we discuss how PTB regulates these disparate processes.